Contestations post-électorales: une alternative dans le processus de démocratisation en Afrique? Exemple du Togo - Abdou, Abdou-Wahabi (Africana Studia, 2020)
After the beginning of the African continent’s democratization process, the people had confidence in elections which were supposed to ensure a regular renewal of the political regimes. However, some regimes in place have been developping strategies to stay in power. For example in Togo, unfulfilled commitments or constitutional amendments to represent in elections are the maneuvers of the “Gnassingbe” regime, which is still in power for more than half a century, despite so-called transparent elections held periodically. As a result, the opposition political parties and the population often resorted to the street demonstrations. These demonstrations date back to the early days of multiparty politics in Togo and are often at the root of several democratic advances, albeit negligible, obtained from the political power in place. This contribution aims to analyze the post-election contestations in Togo and their impact on the country’s democratization process.